2021
DOI: 10.1177/13670069211024747
|View full text |Cite
|
Sign up to set email alerts
|

L1 congruency, word frequency, collocational frequency, L2 proficiency, and their combined effects on Chinese–English bilinguals’ L2 collocational processing

Abstract: Aims: The current study investigated the effects of first language (L1) congruency, word frequency, collocational frequency, second language (L2) proficiency, and their combined effects on L2 collocational processing. Methodology: Twenty English native speakers and 60 adult Chinese–English bilinguals (intermediate and advanced) completed an online phrasal decision task. They made a judgment about whether target word pairs (congruent collocations, incongruent collocations, and non-collocational baseline items) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…The results of the present study support the existence of a dualroute model (e.g., Sosa and MacFarlane, 2002;Wolter and Gyllstad, 2011;Fang and Zhang, 2021), as claimed in previous studies. Furthermore, from the perspective of presentation modality, we were able to show a new way of interpreting the dual-route model.…”
Section: Effect Of Semantic Transparency On Collocational Processing ...supporting
confidence: 93%
See 2 more Smart Citations
“…The results of the present study support the existence of a dualroute model (e.g., Sosa and MacFarlane, 2002;Wolter and Gyllstad, 2011;Fang and Zhang, 2021), as claimed in previous studies. Furthermore, from the perspective of presentation modality, we were able to show a new way of interpreting the dual-route model.…”
Section: Effect Of Semantic Transparency On Collocational Processing ...supporting
confidence: 93%
“…In our experimental design the presentation modality and semantic transparency, or the presentation modality and translational congruency, were fixed factors, respectively. To ensure that semantic transparency and translational congruency did not interfere with each other ( Fang and Zhang, 2021 ), the semantic transparency experiment was conducted on collocations with congruent translation, while the translational congruency experiment was conducted on collocations with low semantic transparency.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study took an initial step toward addressing research questions regarding multiword processing by lowproficiency Japanese English learners. The results for the L1 speakers indicated that L1 English speakers processed syntactically and semantically complete multiword units significantly faster than fragmental ones, even when the The finding that the experimental manipulation was only observed in the accuracy rate of L2 learners is not uncommon in L2 research, especially when participants are lower proficiency learners or have not been immersed in an L2 environment (Fang & Zhang, 2021). In general, timed judgment tasks, such as the present PDT, tap into learners' implicit knowledge (i.e., responding by feeling), while untimed judgment tasks measure their explicit knowledge (i.e., responding by rules) (Ellis, 2005).…”
Section: Discussionmentioning
confidence: 96%
“…Particularly in L2 contexts, accuracy rates may be less precise measures of implicit knowledge than RT data. Instead, accuracy data may be more sensitive to learners' explicit knowledge (see Fang & Zhang, 2021, for a similar discussion). Ellis (2005Ellis ( , 2009 posits that implicit knowledge manifests when participants focus on meaning (i.e., semantic aspect), while explicit knowledge emerges when attention is directed toward form (i.e., grammatical aspect).…”
Section: Discussionmentioning
confidence: 99%